As representações de gênero na formação de professores indígenas Xerente e expressão da violência - Milhomem, Maria Santana Ferreira dos Santos (2010)
Based on the intercultural education studies as well as the cultural studies, this research aims at analysing the social and genre representations, and the expressions of symbolic violence into the teacher's daily work of indigenous Xerente comunity, in order to uncover the processes which sustain the differences, hierarchical relations and prejudice among the members of this socially discriminated group. The research was developed in Tocantínia town, State of Tocantins, Brazil. The approch concerning the construction of identity as a principle of sexual inequality brings in the studies of social categories of genre and indentity construction of men and women, having in mind that they are treated differently since they were born, either because of biological sex or their social and cultural milieu in which they are brought up, reaching its top with expressions of symbolic violence. This study is based on qualitative research, through Life History interviews with 6 (six) female teachers and 2 (two) male chiefs of Xerente ethnic group, besides participant observation, in which can be seen the life and work trajectory and genre representations of this group. The results show that the the daily lives of female Xerentes are organized from changes and permanencies cohabitation. Construct an identity in conflict: sometimes they guide themselves through the values of traditional culture; other times they guide themselves through the values of capitalist occidental culture. On one hand, factors such as higher schooling in the part of women, who take part on political matters, at work, on family economy, opens oportunities to broaden rights and citizenship. On the other hand, more traditional male roles are reaffirmed and seen into men and women's speech in the same proportion in which the growing importance of women in society and politicial organization tends to diminished.